Why Students in Secondary Schools Choose not to do Physics? Implications For Policy and Practice in Developing Countries - Telima Adolphus (European Scientific Journal, ESJ, 2019)
This study investigated the low popularity of physics among secondary school students in Rivers State, Nigeria. One outcome of this situation is concern and interest in effective teaching and learning in the subject in Nigeria. A mixed methods research design was adopted for the study. The study found that teachers’ qualities and resource availability and utilization significantly influence students’ physics enrolment. Also, there was no significant difference in the correlations of teacher and resource factors with enrolment by gender. To boost students’ interest in physics, the study recommended amongst others, that teachers present content in ways that connect physics ideas to the everyday experiences of students and that, policy makers should consider making the study of science compulsory in all classes in secondary schools with the introduction of ‘science for arts’ for the nonscience oriented students.